Pengaruh Akuntabilitas dan Transparansi terhadap Kinerja Keuangan Organisasi Perangkat Daerah (OPD) Kota Bengkulu - Merchilia, Setiandini; Robinson (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to prove the influence of accountability and transparency on the financial performance of regional government organizations in the city of Bengkulu. This research uses a quantitative type of research using primary data. The data collection technique was obtained through a questionnaire, the sampling method used in this research was a sampling census of 30 Regional Apparatus Organizations with representatives of 2 financial employees in each agency. This research uses a multiple linear regression analysis method which is processed using SPSS 25. The research results showed that accountability had a positive and significant effect on financial performance, while transparency had a negative and significant effect on the financial performance of Bengkulu City Regional Apparatus Organizations. It is hoped that this research will have benefits and influence on the development of government agency performance. If the government realizes the importance of an accountable and transparent government on government financial performance.